Respuesta :

Answer:

I graphed both equations to find the solutions.

Step-by-step explanation:

When x is 0, y is -6. When x is 7, y is 8.

x = 0 and 7

Ver imagen 22stolc

Answer: The solutions are

(0, - 6)

(7, 8)

Step-by-step explanation:

The given system of equations is expressed as

y = x² - 5x - 6- - - - - - - - - - - - 1

y = 2x - 6- - - - - - - - - - - 2

We would apply the method of substitution by substituting equation 2 into equation 1. It becomes

x² - 5x - 6 = 2x - 6

x² - 5x - 6 = 2x - 6

x² - 5x - 2x - 6 + 6 = 0

x² - 7x = 0

x(x - 7) = 0

x = 0 or x - 7 = 0

x = 7 or x = 0

Substituting x = 0 into equation 2, it becomes

y = 2 × 0 - 6

y = - 6

Substituting x = 7 into equation 2, it becomes

y = 2 × 7 - 6

y = 14 - 6

y = 8